2019
DOI: 10.1111/jace.16717
|View full text |Cite
|
Sign up to set email alerts
|

Optical transition and luminescence properties of Sm3+‐doped YNbO4 powder phosphors

Abstract: A series of YNbO4: Sm3+ powder phosphors with different doping concentrations were synthesized by a traditional high‐temperature solid‐state reaction method. The crystal structure of the obtained samples was characterized by means of X‐ray diffraction. Concentration quenching, energy‐transfer mechanism, and luminescence thermal stability of YNbO4: Sm3+ samples were studied through the fluorescence spectra and decays. It was concluded that electric dipole‐dipole interaction was the dominant energy‐transfer mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Inorganic luminescent materials have historically attracted considerable attention due to their characteristics such as long decay lifetime [1], easy preparation, low toxicity, and high luminous efficiency [2][3][4]. Rare earth luminescent materials have considerable application potential because of their unique 4f orbit, which can be pumped to excited energy levels to emit colorful light under excitation [5,6].…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic luminescent materials have historically attracted considerable attention due to their characteristics such as long decay lifetime [1], easy preparation, low toxicity, and high luminous efficiency [2][3][4]. Rare earth luminescent materials have considerable application potential because of their unique 4f orbit, which can be pumped to excited energy levels to emit colorful light under excitation [5,6].…”
Section: Introduction mentioning
confidence: 99%
“…Silicate has been widely studied as a satisfactory matrix for fluorescent materials due to its excellent optical properties, chemical stability, and structural diversity [21,22]. On the basis of these advantages, [ 3substitution on the properties of the tungstate matrix fluorescent materials and elucidate the effect of anion substitution on their crystal structures, a series of comparative experiments were conducted to evaluate the different properties after the replacement of the crystal phase and anions in the samples. The luminescence properties of the doped samples were discussed in the three modified matrices, including excitation spectrum, emission spectrum, decay time, chromaticity diagram, and luminescence mechanism of the doped ions in them.…”
Section: Introduction mentioning
confidence: 99%
“…/ 2 , and 11 / 2 ) within 4f n configurations. 23,24 Furthermore, the BiOX (X = F, Cl, Br, or I) compounds would be the proper luminescent hosts for the Sm 3+ ions because the Bi 3+ and Sm 3+ ions possess similar ionic radii and the same charge. To date, the photoluminescence properties of the Sm 3+ -activated BiOCl and BiOBr compounds have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al reported that the Sm 3+ -doped g-C 3 N 4 nanosheets exhibited superior photocatalytic behaviors compared to those of the undoped g-C 3 N 4 nanosheets . In comparison, the Sm 3+ ion, as a member of the rare-earth ions, has been considerably studied as a photoluminescent activator because it can emit red/orange emissions triggered by the 4 G 5/2 → 6 H J transitions ( J = 5 / 2 , 7 / 2 , 9 / 2 , and 11 / 2 ) within 4f n configurations. , Furthermore, the BiOX (X = F, Cl, Br, or I) compounds would be the proper luminescent hosts for the Sm 3+ ions because the Bi 3+ and Sm 3+ ions possess similar ionic radii and the same charge. To date, the photoluminescence properties of the Sm 3+ -activated BiOCl and BiOBr compounds have been reported. , Nevertheless, to the best of our knowledge, there is no research on the photocatalytic activity and photoluminescence characteristics of the Sm 3+ -activated BiOF compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic luminescent materials have historically attracted considerable attention due to their characteristics such as long decay lifetimes [1], easy preparation, low toxicity, and high luminous efficiency [2][3][4]. Rare earth luminescent materials have considerable application potential because of their unique 4f orbit, which can be pumped to excited energy levels to emit colorful light under excitation [5,6].…”
Section: Introductionmentioning
confidence: 99%